Sistema de producción y comercialización y su incidencia en la rentabilidad maderable, del cantón Palenque año 2008-2012, Modelo de gestión. - Arreaga Álvarez, Jesús Jackeline (2013)
The present investigation work was carried out in the properties dedicated to the production forest Teak (Tectona grandis) of the Palenque Town - of The Ríos County. The present titled investigation: "SYSTEM OF PRODUCTION AND COMMERCIALIZATION AND THEIR INCIDENCE IN THE PROFITABILITY MADERABLE, THE PALENQUE TOWN YEARS 2008-2012. GESTION MODEL” she investigates the particularities of the structuring of the production administration and commercialization that carry out the producers and wooden buyers of teak in the Palenque town, their consequences in the productivity and production of the cultivation; and, the economic repercussions in the producers about the profitability of the commercialization of the teak wood. With following objectives: To evaluate the production systems and commercialization and their incidence in the profitability in wood, Palenque town 2008-2012, to identify the systems of production in wood in the Palenque town, to determine the production costs and the point of economic balance of the forest exploitation in the Palenque town, to identify the actors of the productive chain of the wood in The Ríos' county, to investigate the system of more profitable commercialization of the wood, in the respective market. The study was carried out in the forest exploitations that had more than 1 hectare and an approximate population of 9 UPAs understands (productive units) that have begun the process of commercialization of the wood. To be a finite type sample one worked with 100% of the same one. The rising of information was made by means of the pertinent techniques as it represents it: the survey, interviews and direct observation; also, this benefitted and it intermediated by means of the pertinent instruments as they are it: photographic camera and notebook of notes. The results of the investigation were good for the effective application of a model of production administration and wooden commercialization of teak for producing of the Palenque town; model that in their former analysis before it allows improving the production and productivity of their cultivations and the profitability increases for the commercialization of the wood.